Determinant state earnings qualities better than Private Pharmaceutical Companies - Putra, Indra Lukmana; Maulana , Nurefa; Suliswanto , Muhammad Sri Wahyudi (Universitas Muhammadiyah Malang, 2024)
Purpose: Comparative Earning Quality of State and privately pharmaceutical companies listed on Indonesian Stock Exchange (BEI) between 2019-2023 period with liquidity, profitability, solvency and efficiency ratio. Methodology/approach: After collecting the necessary data, appropriate financial ratios and descriptive statistical techniques are used to analyze, interpret and provide a brief overview of the data collected. the comparison involves two state-owned and two privately-owned pharmaceutical discretionary accruals and earnings persistence for earnings quality, and net profit margin, current ratio, debt-to-equity ratio, and total asset turnover for financial performance measurements. Findings: net profit margin, current ratio, debt to equity ratio, dan total asset turnover have significant differences in the variables private are superior to those of state pharmaceutical companies. This recommends the importance of improving earnings quality of State pharmaceutical companies Practical implications: these companies should refrain from earnings manipulation to foster strong and high-quality financial performance, particularly within Indonesia's pharmaceutical sector. Originality/value: This comparison aims to contribute to financial management research by providing insights into the performance of different types of pharmaceutical companies based on earnings quality and financial statement ratios, thus offering academic contributions to the field.